Prevalence of anosmia among COVID-19 patients in Taif City, Kingdom of Saudi Arabia - Mubaraki, Adnan A. (Saudi Med J, 2021)
OBJECTIVES: To assess the prevalence of anosmia in coronavirus-19 (COVID-19) patients. Coronavirus-19-related anosmia and hyposmia is a new emerging concept in the medical literature. METHODS: A retrospective study on COVID-19 patients with anosmia and hyposmia was performed during the period between May-July, 2020. The inclusion criteria were all clinically stable COVID-19 patients >15 years old with positive reverse transcription-polymerase chain reaction (RT-PCR). Patients who refused to participate or leave incomplete questions were excluded. In this study, we investigated 1022 patients who met our criteria. RESULTS: Olfactory dysfunction (OD) was reported by 53% of our COVID-19 patients, of which 32.7% were anosmic and 20.3% were hyposmic. Other neurological symptoms included ageusia (51.4%), fatigue (63%), myalgia (59.2%), and headache (50.9%), all of which showed significant association with OD. In addition, anosmia had a significant association with young age and female gender. However, there was no association between OD and pre-existing neurological disease. CONCLUSION: Half of our COVID-19 patients presented OD (anosmia/hyposmia), which often associated with ageusia and many neurological symptoms.